2016
DOI: 10.1016/j.matlet.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MoS 2 nanoparticles using MoO 3 nanobelts as precursor via a PVP-assisted hydrothermal method

Abstract: a b s t r a c tThe synthesis of MoS 2 nanoparticles from MoO 3 with a certain morphology through a surfactant-assisted hydrothermal process is described in this paper. MoO 3 , which has a nanobelt morphology with a width of 100-500 nm and a length from one to several micrometers, is used as the precursor, and poly(vinylpyrrolidone) (PVP) is used as the surfactant. The morphology of the resulting MoS 2 nanomaterial has been characterized by the field-emission scanning electron microscope, which shows that the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It may also be important to mention that not all commercially available MoS2 is equal, as it was found that the HER properties of MoS2, obtained from different suppliers, varies greatly due to different methods of preparation [13]. Coatings of unique compositions, crystallographic structures, surface morphologies, and catalytic properties, have been synthesized using chemical vapour deposition [14,15], hydro-or solvothermal deposition [16][17][18], the increasingly popular chemical exfoliation method, electrodeposition [19][20][21][22][23], and more. Incorporation of naturally-occurring molybdenite has also been shown to greatly enhance the HER catalytic properties of electrodeposited Ni films in alkaline media [24].…”
Section: Introductionmentioning
confidence: 99%
“…It may also be important to mention that not all commercially available MoS2 is equal, as it was found that the HER properties of MoS2, obtained from different suppliers, varies greatly due to different methods of preparation [13]. Coatings of unique compositions, crystallographic structures, surface morphologies, and catalytic properties, have been synthesized using chemical vapour deposition [14,15], hydro-or solvothermal deposition [16][17][18], the increasingly popular chemical exfoliation method, electrodeposition [19][20][21][22][23], and more. Incorporation of naturally-occurring molybdenite has also been shown to greatly enhance the HER catalytic properties of electrodeposited Ni films in alkaline media [24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the fast factor ( τ 1 ) commonly corresponds to the non-radiative relaxation process, owing to oxide defects, 40 and the slow factor ( τ 2 ) is attributed to the radiative pathway, related to the recombination of photogenerated electron–hole pairs. 41 Furthermore, the average lifetimes ( τ ave ) can be deduced through the following equation for a general comparison of the carrier lifetime: 42 …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the high cost and complex method of preparation restrict them to broad application. In fact, the surfactant-assisted synthesis of MoS 2 has the advantages of low cost, easy operation, and excellent performance, and some surfactants are utilized to optimize MoS 2 -based nanocomposite [11][12][13][14][15]. Sepiolite is a typical clay mineral with the features of environmentfriendly and low cost, which makes it a good carrier for catalyst because the large surface specific area and excellent adsorption are benefit for the high catalytic performance [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%